Non-equilibrium processing of ferromagnetic heavily reduced graphene oxide. (November 2019) - Gupta, Siddharth; Narayan, Jagdish
Abstract: Discovery of ferromagnetism with simultaneous bandgap opening in graphene[1 ] provides an attractive platform towards multifunctional spintronic devices. However, device integration of graphene and reduced graphene oxide (rGO) is hindered by scalability and high temperature required for reducing GO. In this paper, we present a nonequilibrium approach for direct laser writing heavily reduced GO films by melting amorphous carbon in ambient conditions. Nanosecond laser irradiation melts carbon, which regrows into rGO in low undercooling conditions. These rGO films exhibit room-temperature ferromagnetism with a high saturation magnetization of 7.0 emu/g and 40 Oe coercivity. The intrinsic ferromagnetic ordering triggers a broad negative magnetoresistance (MR) cusp from 20 to 50 K. An anomalous crossover from weak localization (WL) to weak antilocalization (WAL) is observed below 5 K, suggesting a substantial enhancement in spin-orbit coupling strength, opening a new route to access topological states in rGO. The rGO films exhibit 12.6 cm 2 /Vs electron mobility with n-type carrier concentration of 1.2 × 10 21 /cc. Raman spectroscopy and temperature-dependent transport investigations in rGO suggest low-disorder, following 2D Mott variable range hopping (VRH) mechanism with a bandgap of ∼0.22 eV and 3 nm localization length. These findings open a definitive pathway for tuning electrical and magnetic properties in graphene-based materials with laser-writing. Graphical abstract: Image 1